Theoretical study of the metallo-porphyrin adsorption on a hematite cluster - Rodríguez, Leonardo; Chirinos, Juan (Ciencia, 1970)
Â  The adsorption geometries of unsubstituted vanadyl porphyrin on a hematite cluster were studied by means of MINDO/SR method. A survey of diatomic pararneters for MINDO was carried out in order to reproduce the experimental values of bond length. Dissociation energy and spectroscopic multiplicity for aii diatomic pairs formed by Fe. V. C, N. H and 0. Models for hematite and unsubstituted vanadyl porphyrin were constructed. Six adsorption geometries were calculated and their adsorption energy curves were plotted. Four adsorption geometries result to be totally repulsive, whereas the two others shown a minirnum value in adsorption energy curve. Nevertheless, only one of these minimum have positive adsorption energy. Thus. only one of the studied geometries represent an effective adsorption site. This geomeúy involves the interaction between an iron atom of the hematite and the Ï€ bond of the pyrrole ring in the metallo porphynn. Due to the softening of some bonds and the changes in the atomic charge of some atoms, we conclude that the adsorption of the metalio porphyrin on a hematite cluster produce the activation of the meco position of the porphyrin for early hydrogenation.